Elucidation of Arctigenin Pharmacokinetics and Tissue Distribution after Intravenous, Oral, Hypodermic and Sublingual Administration in Rats and Beagle Dogs: Integration of In Vitro and In Vivo Findings - Li, Jie; Li, Xin; Ren, Yu-Shan; Lv, Yuan-Yuan; Zhang, Jun-Sheng; Xu, Xiao-Li; Wang, Xian-Zhen; Yao, Jing-Chun; Zhang, Gui-Min; Liu, Zhong (Frontiers in Pharmacology, 2017)
Although arctigenin (AG) has diverse bioactivities, such as anti-oxidant, anti-inflammatory, anti-cancer, immunoregulatory and neuroprotective activities, its pharmacokinetics have not been systematically evaluated. The purpose of this work was to identify the pharmacokinetic properties of AG via various experiments in vivo and in vitro. In this research, rats and beagle dogs were used to investigate the PK(pharmacokinetics, PK) profiles of AG with different drug-delivery manners, including intravenous (i.v), hypodermic injection (i.h) and sublingual (s.l) administration. The data shows that AG exhibited a strong absorption capacity in both rats and beagle dogs (absorption rate < 1 h), a high absorption degree (absolute bioavailability> 100%), and a strong elimination ability (t1/2< 2 h). The tissue distributions of AG at different time points after i.h showed that the distribution of AG in rat tissues is rapid (2.5 hours to reach the peak) and wide (detectable in almost all tissues and organs). The AG concentration in the intestine was the highest, followed by that in in the heart, liver, pancreas and kidney. In vitro, AG were incubated with human, monkey, beagle dog and rat liver microsomes. The concentrations of AG were detected by UPLC-MS/MS at different time points (from 0 min to 90 min). The percentages of AG remaining in four species’ liver microsomes were human (62 ± 6.36 %) > beagle dog (25.9 ± 3.24 %) > rat (15.7 ± 9 %) > monkey (3.69 ± 0.12 %). This systematic investigation of pharmacokinetic profiles of arctigenin (AG) in vivo and in vitro is worthy of further exploration.